ADAPTATION OF AGILE MANAGEMENT FOR NATURE BASED INFRASTRUCTURE PROJECTS - Rahayu Mahardikaningsih; Siti Rochani; Fayola Issalillah; Didit Darmawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The adoption of Nature Based Solutions for infrastructure projects demands a management approach capable of responding to dynamic environmental conditions. This qualitative literature study explores how agile management principles can be adapted for NbS project execution. The analysis covers iterative planning, cross functional team structures, high frequency monitoring, flexible budgeting, and responsive procurement procedures. Findings indicate that successful implementation requires simultaneous reform across all five aspects due to their interdependencies. Conventional project management frameworks embedded in government regulations present significant barriers to agility. The study proposes a conceptual framework for agile management in NbS projects that can serve as a reference for policymakers and project managers. This framework prioritizes value based measurement of success over adherence to initial plans. Technology integration particularly environmental sensors and drone based monitoring emerges as a critical enabler for rapid response capabilities. The conclusions suggest revising existing infrastructure project guidelines to accommodate iterative planning and flexible resource allocation.